ANALISIS KEMAMPUAN SISWA DALAM MENGARANG PUISI BERTEMA CINTA TANAH AIR PADA SMP KABUPATEN PIDIE JAYA - Teuku Mahmud (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2019)
Kurangnya pendidikan tentang cinta tanah air merupakan salah satu penyebab kurangnya rasa cinta para pemuda kepada negara. Para pemuda tidak memahami bahkan tidak mengetahui makna dari nasionalisme itu sendiri. Padahal sebagai generasi penerus, para pemuda berkewajiban untuk memahami negaranya terlebih dahulu. Ini merupakan salah satu cacat yang cukup mendasar dan menganga lebar, sebab bagaimana para pemuda dapat mencintai negaranya sendiri bila mereka tidak perduli dan mengerti tentang perjuangan, landasan dan asal –usul negara ini berdiri. Berdasarkan hal tersebut Peneliti ingin menganalis sejauh mana pengetahuan para siswa dalam memahami makna cinta tanah air dengan melakukan tes terhadap siswa tersebut. Namun agar siswa lebih tertarik mengikuti tes tersebut peneliti membuat tes dalam bentuk puisi. Dalam hal ini siswa harus mengarang sebuah puisi dengan tema cinta tanah air. Dari hasil tes tersebut akan diketahui sejauh mana pemahaman siswa dalam memaknai arti cinta tanah air. Penelitian ini dilaksanakan di SMP Kabupaten Pidie Jaya. Teknik Pengumpulan Data dengan menggunakan metode observasi, wawancara, dan studi dokumentasi. Data dianalisis dengan deskriptif kualitatif yaitu dengan análisis data, data collection, reduksi data, display data, dan penarikan kesimpulan. Diharapkan dengan hasil penelitian ini dapat diketahui besar ataupun kecilnya rasa cinta tanah air para siswa yang mewakili generasi penerus bangsa. Abstract Lack of education about the love of the motherland is one of the causes of the lack of a sense of love for the youth to the country. The youths do not understand not even knowing the meaning of nationalism itself. But as the next generation, the young men are obligated to understand his country first. This is one of the defects that are pretty basic and gaping wide, for how these young men can love their own country when they don't really care and understand about the struggles, the runway and the origin – the country's proposal stands. Based on these Researchers want to analyze the extent to which the knowledge of the students in understanding the meaning of love for the homeland by performing tests against the students. But in order to make students more interested in following the tests researchers make a test in the form of poetry. In this case students should compose a poem on the theme of love of the motherland. From the test results will be known the extent to which students in understanding to interpret the meaning of love. From the test results will be known the extent to which students in understanding to interpret the meaning of love. The research was conducted in Pidie Jaya Junior High School. The technique of Data collection by using the methods of observation, interviews, and documentation study. Data were analyzed with descriptive qualitative data, i.e. análisis data collection, reduction of data, display data, and the withdrawal of the conclusion. Expected with results of research can be large or small taste known to love the motherland students who represent the next generation of the nation. Keywords: Analysis, Capability, Fabricate, Poetry